Results of 24 hours’ monitoring of blood pressure in women with hypertension in postmenopause depending on bone mineral density - T A Raskina; I. V. Filatova (Научно-практическая ревматология)
To assess results of 24 hours’ monitoring of blood pressure (MBP) in women with hypertension (H) in postmenopause depending on bone mineral density (BMD). Material and methods. 50 women with confirmed diagnosis of H with duration more than a year (main group) and 27 women without H of comparable age. BMD was evaluated with dual-energy x-ray absorptiometry (bone densitometer Excell XR-46 (Norland, USA) using T criterion (WHO, 1994). MBP was performed with monitor MnCDP (BPLab, Russian Federation). Statistical analisis was done with “Statistica” 6.0 (StatSoft, USA) Results. T criterion values in women with H were significantly lower than in women with normal blood pressure. Mean T-criterion in women with H was -1,47± 1,05, and without H —0,79±0,85 (p=0,003). Women with osteopenia had circadian rhythm of diastolic blood pressure “non-dipper”.